1997
DOI: 10.1161/01.res.80.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Biochemical Analysis of Angiotensin II–Forming Pathways in the Human Heart

Abstract: Blockade of the renin-angiotensin system by inhibition of angiotensin-converting enzyme (ACE) is beneficial for the treatment of hypertension and congestive heart failure. However, it is unclear how complete the blockade by ACE inhibitors is and if there is continuing angiotensin II (Ang II) formation during chronic treatment with ACE inhibitors. Indeed chymase, a serine protease, which is able to form angiotensin II from angiotensin I (Ang I) and cannot be blocked by ACE inhibitors, has been shown to be prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
137
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(141 citation statements)
references
References 39 publications
1
137
0
2
Order By: Relevance
“…Alternative pathways to renin cleavage of angiotensinogen are not thought to be of any great physiological importance, 32 whereas a substantial proportion of tissue Ang II is generated by non-ACE pathways. 33,34 Hence, it has been proposed that more effective blockade of tissue Ang II formation may occur with renin inhibition than with ACE inhibition. 35 Further differences between renin inhibition, ACE inhibition, and angiotensin receptor blockade could arise from disparate effects on circulating and tissue levels of bioactive Ang peptides and different patterns of stimulation of the various receptor subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative pathways to renin cleavage of angiotensinogen are not thought to be of any great physiological importance, 32 whereas a substantial proportion of tissue Ang II is generated by non-ACE pathways. 33,34 Hence, it has been proposed that more effective blockade of tissue Ang II formation may occur with renin inhibition than with ACE inhibition. 35 Further differences between renin inhibition, ACE inhibition, and angiotensin receptor blockade could arise from disparate effects on circulating and tissue levels of bioactive Ang peptides and different patterns of stimulation of the various receptor subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that non-ACE pathways are, by inference, responsible for about 40% of Ang II generation in the intact human kidney [86] and that chymase is the dominant Ang II-generating pathway in the human heart, coronary arteries, and atherosclerotic aorta in vitro [85,87,88]. It has thus been proposed that abnormal activation of the tissue RAAS may contribute to the pathogenesis of cardiovascular disease even in the absence of derangements in the circulating system [89].…”
Section: Raas Overviewmentioning
confidence: 99%
“…Until now, there have been many reports of peptides with respect to analysis of drugs in plasma using column switching techniques [13][14][15]. Analysis of ANG peptides has been performed using HPLC combined with radioimmunoassay [16][17][18][19]. Liquid chromatography-mass spectrometry (LC-MS) features high selectively and high sensitivity.…”
Section: Introductionmentioning
confidence: 99%